Effects of lubricated surface in the stagnation point flow of a micropolar fluid - Mahmood, K.; Sajid, M.; Ali, N.; Arshad, A.; Rana, M.A. (Pusat Pengajian Sains Matematik, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
In this investigation, we have considered a steady, two-dimensional flow of a micropolar fluid towards a stagnation point over a lubricated plate. A power law fluid is utilized for the purpose of lubrication. To derive the slip condition in the present flow situation, continuity of shear stress and velocity has been imposed at the fluid lubricant interface. The set of nonlinear coupled ordinary differential equations subject to boundary conditions is solved by a powerful numerical technique called the Keller-box method. Some important flow features have been analyzed and discussed under the influence of slip parameter , material parameter and ratio of micro-rotation to the skin friction parameter . The main purpose of the present article is to analyze the reduction in the shear stress and couple stress effects in the presence of lubrication as compared to the viscous fluid that may be beneficial during polymeric processing.